La mimesi invertita: Inversione di genere e condanna del teatro nel pensiero di Platone - Marinelli, Manlio (Mimesis Journal, 2024)
This article aims at examining the Greek point of view about the close, complex and disturbing relationship between role and gender in ancient Greek performance. The author proposes different sources, particularly several parts excerpted from Republic and Laws of Platon and the Fisiognomica of Pseudo-Aristotle. The analysis underlines a strong contradiction: in the practice of body and gesture, male and female elements are inextricably mixed but Greek authors wish they are separated with the aim of stating the superiority of male identity.